(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
The Spanish Civil War represented a turning point in the Western world, with regard to the traditional methods and techniques used by Museum curators to protect and preserve the Artistic Heritage. The Republic governments started up, between 1936 and 1939, a detailed project to save the Spanish heritage. This project was a response to the high importance that culture had for Republican elites. During the last months of the Civil War, contradictions developing the project emerged leading to important controversies that are nowadays still unsolved. These problems incited the dispersion as well as the destruction of an important part of the Artistic Heritage, which had been kept safe during the conflict. The works of art in question were part of the cargo that the yacht Vita shipped to Mexico.